PENGEMBANGAN MODUL MENULIS SURAT BISNIS BAHASA INGGRIS UNTUK KELAS XII SEKOLAH MENENGAH KEJURUAN - Diselita, Susi -; -, Rachmawati -; -, Saharudin - (Program Magister Teknologi Pendidikan Universitas Jambi, 2011)
This research is aimed at developing a module of writing business letters in English for twelfth grader of vocational school. The module is developed by using Dick’s et al. (2005) development model. This research used only 9 com-ponents of the model. In the vocational school module is one important alternatives for delivering material to the students. Validation of the module are conducted by the experts (material and media), an English teacher, and the students. The validation result from the experts state that the module is good, according to the contents of the module is applicable for the students, the technique of writing of the module is good, and language composing is good. The English teacher, as the user of the product, states that this module is clear, interesting, appropriate, effective and easy to use. From the one-to-one evaluation, small group evaluation, field trial, the attitude questionnaires, interviews and observations indicate that the module is good, interesting and appropriate for them. It can be concluded that the module can be used in learning English in twelfth grader of vocational school. Keywords: module, business writing, development model